Intensi Penggunaan QRIS Berdasarkan Technology Acceptancy Model Pada UMKM Kuliner Kota Padang Provinsi Sumatera Barat - Idwar, Idwar; Rosa, Yenni Del; Sari, Melati Nilam; Nesa, Nesa (CV. ITTC INDONESIA, 2024)
The aim of the research is to determine the partial influence of perceived ease to use, perceived usefulness, attitude toward using and actual usage on the turnover of culinary MSMEs in the city of Padang. Primary data in the form of a questionnaire comes from field research. This type of research is associative with a quantitative approach. The research population was 4,454 culinary MSMEs in the city of Padang who already had a Business Identification Number (NIB). The number of research samples of 100 MSMEs was determined using the Rao Purba formula with a simple random sampling technique. Data collection methods were carried out using questionnaires, interviews and observations. All instrument tests and classical assumption tests are met before the data is processed. all research independent variables are perceived ease to use (X1), perceived usefulness (X2), attitude toward using (X3) and actual usage (X4). Multiple linear regression results Y = 104,631 + 97,106X1 + 89,735X2 + 90,358X3 + 78,469X4 + e where Y = turnover. Partial and simultaneous hypothesis testing at a significance level of 5% shows that perceived ease to use, perceived usefulness, attitude toward use and actual usage have a significant positive effect on the turnover of culinary MSMEs in the city of Padang, West Sumatera province.